2016
DOI: 10.1049/htl.2016.0043
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac ultrasonography over 4G wireless networks using a tele‐operated robot

Abstract: This Letter proposes an end-to-end mobile tele-echography platform using a portable robot for remote cardiac ultrasonography. Performance evaluation investigates the capacity of long-term evolution (LTE) wireless networks to facilitate responsive robot tele-manipulation and realtime ultrasound video streaming that qualifies for clinical practice. Within this context, a thorough video coding standards comparison for cardiac ultrasound applications is performed, using a data set of ten ultrasound videos. Both ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Image Current ultrasonic robot technology has made considerable advances, and rich experience has been accumulated through many clinical applications. [13][14][15][16][17][18][19][20][21]33 Studies have indicated that the quality of images captured by robot-assisted remote ultrasound systems correlate well with those captured by conventional ultrasound. [34][35][36] Robot technology has been reported for assistance in the diagnosis and treatment of lung diseases previously, [37][38][39] but the application of a 5G-based robot-assisted remote ultrasound system for use in lung disorders has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image Current ultrasonic robot technology has made considerable advances, and rich experience has been accumulated through many clinical applications. [13][14][15][16][17][18][19][20][21]33 Studies have indicated that the quality of images captured by robot-assisted remote ultrasound systems correlate well with those captured by conventional ultrasound. [34][35][36] Robot technology has been reported for assistance in the diagnosis and treatment of lung diseases previously, [37][38][39] but the application of a 5G-based robot-assisted remote ultrasound system for use in lung disorders has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Over the past 20 years, advances in computer networks, multimedia, and communication technologies have led to the development of remote ultrasonic robot technology for clinical applications, and a wealth of experience has been accumulated in abdominal, cardiac, pelvic, obstetric, vascular, and thyroid examinations. [13][14][15][16][17][18][19][20][21] The lack of contact requirement and continuous improvements in safety performance have led to its application for examination of patients with COVID-19 in isolation wards, as it can help to protect examiners against viral infection. In the current study, a 5G-based robotassisted remote-operated ultrasound system was used for remote examination of patients with COVID-19.…”
mentioning
confidence: 99%
“…Coarse translational positioning of the robot is handled by a human assistant, while fine adjustments of probe orientation are remotely controlled by the expert sonographer via a haptic device with force feedback. MELODY has already been used for cardiac [ 14 ], abdominal [ 15 , 16 ], obstetric [ 15 , 17 •], pelvic, and vascular telesonography [ 15 ] in over 300 patients.
Fig.
…”
Section: Teleoperationmentioning
confidence: 99%
“…In this regard, teleoperated surgery has been widely investigated and commercialized. Yet, telemedicine applications also include various new remote services (whose interest grows during pandemics), such as a simple consultation or an expertise with a specific healthcare professional, telemonitoring/diagonosis [9], or an assistance for a particular procedure or examination [10][11][12][13][14][15][16][17][18][19], over telecommunication networks.…”
Section: Introduction 1telerobotics General Contextmentioning
confidence: 99%